Standard-based assessment of foreign languages and washback effect - Azucena Gozalo Ausín (ADIDE Federación, 2014)
In the field of education terms such as "assessment" and "standardization" seem to be loaded with a somewhat negative connotation. In this article I intend to present a standard-based proposal of assessment of communicative competence in foreign languages whose main objectives are promoting awareness into the nature of the teaching-learning process, fostering a competence-based approach and providing a universally intelligible set of reference levels of language acquisition in the Spanish school system. The fruitful collaboration between different educational agents and the application of the Standardized Tests of English in each and every educational institution in Cantabria where Primary and Compulsory Secondary Education are taught have brought about a decisive step forward towards the assessment and international recognition of levels of achievement. It is my contention that this proposal has had a definitely positive backwash effect in the process of teaching and learning foreign languages in our school system.